The Antimicrobial Effects of Alcoholic Leaves Extract of Salvia Officinalis Against Multidrug Resistant Pseudomonas Aeruginosa - Sweedan, Enass Ghassan (Iraqi Journal of Science, 2021)
Two isolates of Pseudomonas aeruginosa were isolated from patients with Urinary Tract Infection (UTI). The aim of this study was to determine the antimicrobial effect of alcoholic leaves extract of Salvia officinalis on Multidrug resistant (MDR) P. aeruginosa. Using the well diffusion test, the alcoholic leaves extract at 100mg/ml and 200 mg /ml was shown to possess antimicrobial activity against the tested microorganism. The inhibition zones of S. officinalis at 200 mg/ml, and 100 mg/ml of the extract showed diameters of 23mm and 20mm, respectively. But the diameters of the inhibition zones caused by treatment with the antibiotics Ciprofloxacin, Ticarcillin + Clavulanic acid, and Cefotaxime were 28mm, 27mm, and 25mm) for both isolates, respectively. The results indicate that P. aeruginosa was resistant to most antibiotics of different groups used in this study. It was found that the isolates were Multidrug Resistant (MDR) by sensitivity test. The results of minimum inhibitory concentration (MIC), by using E-test strips, showed that MIC of Cefoxitin was 4Âµg/ml for P. aeruginosa 1, but P. aeruginosa 2 was resistant. MIC value for Cefoperazone was 8Âµg/ml against P. aeruginosa 1, whereas P. aeruginosa 2 was resistant. MIC value was also determined for the alcoholic leaves extract against P. aeruginosa, showing a value of 100 mg/ml, while the plant extract also had synergistic effects with Ciprofloxacin, Cefotaxime, and Ticarcillin+ Clavulanic Acid. It can be concluded that the alcoholic leaves extract of S. officinalis had considerable antimicrobial effects on MDR P. aeruginosa. Thus, it can be used instead of antibiotics for the treatment of UTI caused by MDR P. aeruginosa to reduce the side effects of antibiotics. On the contrary, its use with antibiotics enhances their action without interfere with them.